Fertility, fecundity and gonadosomatic index of Poecilia reticulata (Pisces: Poeciliidae) in Heredia, Costa Rica - Urriola Hernández, Mario; Cabrera Peña, Jorge; Protti Quesada, Mauricio (Revista de Biología Tropical, 2004)
Between September and November of 1998, 1 432 females of Poecilia reticulata were collected in a pond in Santo Domingo, Heredia, Costa Rica. The average total length of females was 34.43 ± 7.26 mm (range 17.80 and 51.50 mm) and the average total weight of 0.69 ± 0.48 g (range 0.06 and 2.32 g). This species is a viviparous matrotrofic and the specimens were sexually mature. The total length-fertility relationship was F = 0.527e 0.1171Lt (r2 = 0.9404). The average fertility was 56.1 ± 43.6 (eggs + embryos) (range 8.0 and 197.6). The total length-fecundity relationship was Fo = 0.695e 0.1076 Lt (r2 = 0.9376). The average fecundity was of 49.0 ± 36.0 (oocytes + ova) (range 7.0 and 179.0). The total length-gonadosomatic index relationship was IGS = 0.0014 e0.134 Lt (r2 = 0.8581). The average gonadosomatic index was 0.25 ± 0.27% (range 0.02 and 1.31%). Rev. Biol. Trop. 52(4): 945-950. Epub 2005 Jun 24.